Instagram as an Educational Tool for Autonomous Learning: Pre-Service EFL Teacher’s Voices - Putra, Tandi Rahmanda; Madkur, Ahmad (Borneo Journal of Language and Education, 2025)
Instagram has become an essential tool for language learners outside of the classroom, in addition to creating new avenues for social networking. Some researchers have investigated the use of Instagram for self-directed learning, but research and knowledge on the extent to which Instagram can promote learner autonomy among preservice teachers of English as a foreign language (EFL) remain under-explored. The purpose of this study is to investigate how EFL pre-service teacher use Instagram to support student autonomy in their English language learning, particularly in light of the growing trend of digitalization in education. Fifteen EFL PSTs from an Islamic university in the province of Lampung, Indonesia were involved as participants of this qualitative study. The findings show that the participants viewed Instagram as useful alternative platform for learning English. They employed various creative strategies to utilize Instagram’s features, including enhancing vocabulary, grammar comprehension, and speaking skills. However, they also encountered challenges, such as distractions from non-educational content and connection issues. Despite certain limits of this platform, they also viewed learning English on Instagram as a pleasant experience. The study concludes that Instagram, when used wisely, can be a good platform to promote autonomous learning in ELT, especially in the context of growing educational digitalization.